Tobacco-Specific Nitrosamines in Electronic Cigarettes: Comparison between Liquid and Aerosol Levels - Farsalinos, Konstantinos E. (Int J Environ Res Public Health, 2015)
Introduction: Although electronic cigarette (EC) liquids contain low levels of tobacco-specific nitrosamines (TSNAs), studies evaluating the levels emitted to the aerosol are scarce. The purpose of this study was to compare the levels of TSNAs between liquids and generated aerosol. Methods: Three EC liquids were obtained from the market. An additional (spiked) sample was prepared by adding known amounts of standard TSNAs solutions to one of the obtained liquids. N-nitrosonornicotine (NNN), N-nitrosoanatabine (NAT), N-nitrosoanabasine (NAB) and 4-(methylnitrosamino)1-(3-pyridyl)-1-butanone (NNK) were measured. Three 100-puff sets from each liquid were trapped in filter pads and were subsequently analyzed for the presence of TSNAs. The expected levels of TSNAs (calculated based on the liquid consumption) were compared with the measured levels in the aerosol. Results: Only NAB was found at trace levels in two commercial liquids (1.2 and 2.3 ng/g), while the third contained 1.5 ng/g NAB and 7.7 ng/g NNN. The 100-puff sets resulted in 336–515 mg liquid consumption, with no TSNAs being detected in the aerosol. The spiked sample contained 42.0–53.9 ng/g of each of the TSNAs. All TSNAs were detected in the aerosol with the measured levels being statistically similar to the expected amounts. A significant correlation between expected and measured levels of TSNAs in the aerosol was found (r = 0.83, p < 0.001). Conclusion: The findings of this study show that exposure of EC users to TSNAs can be accurately assessed based on the levels present in the liquid, without the need to analyze the aerosol.